LEGAL ISSUES ON TEMPORARY PROTECTION BEFORE JUDGMENT AND ENFORCEMENT UNDER THE CODE OF CIVIL PROCEDURE - Poomipong, Rachapong; Wongkarasin, Boonyalit (Journal of MCU Nakhondhat, 2025)
This research aims to study the legal problems in temporary protection in the case of emergency requests under the Civil Procedure Code. The study is about the court’s discretion in issuing temporary protection requests and emergency requests that affect the plaintiff who filed the request in the case and to study the impact of the court dismissing the request for temporary protection in the case of the plaintiff filing the request in the emergency in order to determine the guidelines for amending the law so that the plaintiff can benefit from the provisions of the law and to be consistent with the intention of the law. The research results show that the Civil Procedure Code, in the part of temporary protection before judgment and enforcement, still does not have sufficient legal measures to provide temporary protection in the emergency for the plaintiff, as follows: 1) The Civil Procedure Code, in the part about temporary protection in the emergency, gives the court too much discretion in considering the emergency request, which results in the plaintiff not receiving immediate temporary protection when the plaintiff requests it. 2) The Civil Procedure Code does not adequately protect the plaintiff’s rights when the court issues an order dismissing the emergency request. The law prohibits a plaintiff from filing another emergency request during the court’s proceedings, even after a legal emergency emergency. and 3) A plaintiff cannot file an emergency injunction request outside of office hours, which means that the plaintiff will not receive immediate temporary protection during the court’s proceedings when a legal emergency has occurred. Therefore, the law should be amended in this regard.